Process Validation as a Critical Enabler in Pharmaceutical Manufacturing - Ale, Narendar Kumar (Journal of Research in Science and Engineering, 2026)
Process validation is an ongoing programme, essential part of GMP and by aligning process validation operations with the product lifecycle, the pharmaceutical industry ensures that its processes are reliable and consistent over the whole duration of their commercialization. This game-changing practice minimizes risks, reduces costs, and supports continuous improvement, enhancing patient safety and meeting stringent industry standards.